Calculation of the Concentrations of Depleted Uranium in The Diyala River Sediment Samples Using The Nuclear Track Detector CR-39 - Subhi, Auday T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study, depleted uranium concentrations were calculated in sediments Diyala River samples , where 14 samples of sediment along the Diyala River were collected , starting from the Rustumiya area and ending with the Tuwaitha area after its confluence with the River Tigris , using the solid - state nuclear track detectors technique (SSNTDs). We found that the highest concentration of depleted uranium was in the sample (A-13), and was taken from the Tuwaitha area with the specific activity of the amount (78.1 ± 8.5 Bq/kg ) and the lowest concentration of the depleted uranium was in the sample (A-7), and was taken from the Azwaip area with the specific activity of the amount (46.3 ± 8.2 Bq/kg ) and the average up to (61.13 ± 5.26 Bq/kg ). The results showed that the average hazard index of these samples was up to (0.341) which is the limit being less than 1 and converged with what is recorded in some international organizations such as the (WHO) and (EPA). The results also show that external effective dose average was around (0.0325 mSv/y) and the internal effective dose average was around (0.182 mSv/y) .